Cytomegalovirus uveitis in HIV-infected patients: the main clinical forms - T. D. Sizova; V. M. Khokkanen; E. V. Boiko (Российский офтальмологический журнал)
Effective treatment of HIV-infected patients has changed the previous view of the clinical picture of cytomegalovirus uveitis (CMV uveitis).Purpose: to determine the prevalence and structure of clinical forms of CMV uveitis in HIV-infected patients.Material and methods. 66 patients (97 eyes), aged 39.6 ± 3.91, were diagnosed with stage 4c HIV infection. In 35 patients (53%), the duration of infection exceeded 5 years, in 13 patients (19.7%), it exceeded 10 years, and another 13 patients (19.7%) had the condition for over 15 years. The ophthalmological follow-up of patients diagnosed with CMV uveitis ranged from 6 months to 13 years (the median of 45.5 months).Results. By the time CMV uveitis was detected, the median CD4 cell count was 34 cells/μL (the norm being 570–1100 cells/μL). The content of whole blood CMV DNA was 2.43 lg copies/105 cells. The main form of the disease was chorioretinitis, diffuse and generalized forms of the disease were diagnosed in 68.0% of cases. In predicting visual acuity, the leading regression criterion was the clinical form of the disease.Conclusion. Diffuse and generalized forms of the disease prevailed in clinical practice. The prevalence of chorioretinal lesion determined visual acuity, which in 39.2% of the eyes met the criteria for blindness according to the WHO classification (1977)